Modern Slavery: The Hot Potato for Organizations in the Absence of Global Coordinated Action - Krambia-Kapardis, Maria; Clark, Colin (My University, 2024)
This conceptual chapter reviews the international legislative frameworks and tests two research questions relating to eradicating modern slavery (MS) within the United Nations Sustainable Development Goals (SDGs). The legislative review indicates that, internationally, legislators have not used the concept of MS consistently, nor have they been consistent in the scope of the reporting entities subject to MS legislation. Based on their review, the authors found that the legislative and regulatory initiatives undertaken to eradicate MS globally lack homogeneity, consistency, and synergies. Some address MS broadly, while others take a narrower scope (e.g., focusing on child labor alone). Some countries take a risk-based approach with due diligence reviews, while others place the onus on businesses and other organizations to report their MS statements. Thus, while reporting entities around the globe are subject to different compliance requirements, the social problem remains. The authors also determined that, in seeking to meet the SDGs relating to MS legislative measures, the 4Ps framework (Organization for Security and Co-operation in Europe 2003, cited in Friedman, 2021) of prosecuting, protecting, preventing, and policing was not fulfilled. A global, coherent, holistic approach is recommended if businesses and other organizations are to contribute towards meeting the SDGs by 2030.
Keywords: Modern Slavery; Legislative Measures; Prevention; 4Ps; UN Sustainable Development Goals